Pre- and Posttherapy Assessment of Intestinal Soluble Mediators in IBD: Where We Stand and Future Perspectives - F. Scaldaferri; V. Petito; L. Lopetuso; G. Bruno; V. Gerardi; G. Ianiro; A. Sgambato; A. Gasbarrini; G. Cammarota (Hindawi Limited, 2013)
Inflammatory bowel disease (IBD) is a chronic inflammatory condition characterized by an abnormal immune response against food or bacterial antigens in genetically predisposed individuals. Several factors of innate and adaptive immune system take part in the inflammatory process, probably actively contributing in endoscopic and histological healing at molecular level. Although it is difficult to discriminate whether they are primary factors in determining these events or they are secondarily involved, it would be interesting to have a clear map of those factors in order to have a restricted number of potentially "good candidates" for mucosal healing. The present review will present a class of these factors and their modulation in course of therapy, starting from pathogenic studies involving several treatments associated with good clinical outcomes. This approach is meant to help in the difficult task of identifying "good candidates" for healing signatures, which could also be possible new therapeutic targets for clinical management of IBD patients.